Economically reproducible surface-enhanced Raman spectroscopy of different compounds in thin film - Islam, Ahatashamul; Tasneem, Fariha; Khan, Zulfiqar Hasan; Rakib, Asif; Farhad, Syed Farid Uddin; Talukder, Aminul I; Haider, AFM Yusuf; Md Wahadoszamen, - (Journal of Bangladesh Academy of Sciences, 2021)
We report herein an economically cheap and functionally stable surfaceenhanced Raman scattering (SERS) protocol of two photoactive pigments Rhodamine 6G (R6G) and Kiton Red (KR), implemented in thin films of silver (Ag) and gold (Au) nanoparticles (AgNPs and AuNPs). Both commercially available and chemically synthesized nanoparticles were used. The suitability of the nanoparticles toward SERS activity was tested through UV-visible absorption spectroscopy and scanning electron microscopy (SEM). The AgNPs and AuNPs based SERS substrates in the form of films were fabricated onto square-sized aluminum(Al) plates by simple drop deposition of colloidal nanoparticles solution onto their polished surfaces. The prepared nanoparticle films were sufficiently dried and coated further with the probe (R6G and KR) molecules by employing the identical deposition technique. The enhanced Raman signals of R6G and KR in such composite film structures were then recorded through a custom-built dispersive Raman spectrometer with He-Ne laser excitation at 632.8 nm. Our AgNPsfilm-based SERS protocol could yield the magnitude of the Raman signal enhancement up to 104 times for both R6G and KR. Moreover, AuNPs-based film was found to be less efficient toward the Raman enhancement of both compounds. Our SERS substrates can be easily fabricated, and SERS spectra are reproducible and stable, allowing one to consistently get a reproducible result even after 6 months. J. Bangladesh Acad. Sci. 45(1); 1-11: June 2021